2015
DOI: 10.1057/ejdr.2015.10
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Segregation in the Indian Labour Market

Abstract: This article measures the extent of occupational segregation for gender and social groups in India. It is based on a recent round of a nationally representative employment and unemployment survey of the Government of India. We use overall and local measures of occupational segregation. We find that occupational segregation for both genders and social groups is higher in the urban sector than in the rural sector. Females are more segregated than their male counterparts in both sectors. Among social groups, sche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 35 publications
(33 reference statements)
2
17
0
Order By: Relevance
“…These restrictions limit women to taking jobs close to home, and coupled with little education, result in domestic and home-based work that is poorly compensated and encourages little empowerment. Gender segregation in occupations for women has been documented in India, emphasizing domestic and service jobs (Agrawal, 2016). These professions are also more concentrated among women of lower socioeconomic class and with less education, reinforcing the cycle of poverty through limited economic opportunity and low-paying work (Sarkar, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…These restrictions limit women to taking jobs close to home, and coupled with little education, result in domestic and home-based work that is poorly compensated and encourages little empowerment. Gender segregation in occupations for women has been documented in India, emphasizing domestic and service jobs (Agrawal, 2016). These professions are also more concentrated among women of lower socioeconomic class and with less education, reinforcing the cycle of poverty through limited economic opportunity and low-paying work (Sarkar, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The extent of occupational segregation for gender and social group in India was examined by Tushar Agrawal [15] and concluded that occupational segregation and social group segregation were higher in urban sectors than in the rural sectors especially among females. Across the social group, the segregation was higher among scheduled caste and scheduled tribes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, many of these debates have been theoretical or have used anecdotal evidence rather than being substantiated by recent empirical data (Agrawal, 2016;Cotterill et al, 2014;Vaid, 2014) by Dalits and Adivasi tend to be very small, less likely to employ labor from outside the family, and more likely to belong to the informal or unorganized sector.…”
Section: Caste-related Issues In Rural Indiamentioning
confidence: 99%
“…Similarly, in most of the villages, the same caste (Vaishya, e.g. Mahajan) also has complete control over credit, and they charge a usurious interest rate from illiterate and helpless lower castes (Agrawal, 2016;Shah et al, 2007). Moreover, as caste structure is deeply entrenched, most of the government officials, including Gram Sevak, 25 do not provide any support to lower castes, and in many cases actually exploit their ignorance and gullibility.…”
Section: Caste-related Issues In Rural Indiamentioning
confidence: 99%
See 1 more Smart Citation